Molecularly imprinted β‐cyclodextrin/Kaoline particles for the selective recognition and binding of bisphenol A. (25th July 2013) - Xie, Qingjie; Li, Linzi; Pan, JianMing; Meng, Minjia; Song, Zhilong; Zhu, Wenjing; Wang, Bing; Yu, Ping
Abstract Molecularly imprinted β‐cyclodextrin/Kaoline particles (MIPs) were prepared for recognitive adsorption of bisphenol A (BPA) from aqueous solution. The characterisation of MIPs were achieved by FTIR spectra, SEM micrographs, nitrogen adsorption–desorption analysis and elemental analysis. The equilibrium data, at various temperatures, were described by the Langmuir, Freundlich and Dubinin‐Radushkevich isotherm models. The kinetic properties were successfully investigated by pseudo‐first‐order model, pseudo‐second‐order model, intraparticle diffusion equation, initial adsorption rate and half‐adsorption time. Based on the comparison of diffusion parameters, including intraparticle diffusion, film diffusion and pore diffusion, we can confirm the process of recognitive binging sites in MIPs. A diffusion‐controlled process as the essential adsorption rate‐controlling step was proposed. Moreover, intraparticle diffusion increased with BPA concentration while film and pore diffusion decreased. An increase in the temperature was found to increase intraparticle and pore diffusion, and reduce film diffusion. The selectivity of MIPs also demonstrated higher affinity for target BPA over competitive phenolic compounds than that of non‐imprinted polymers (NIPs).